Variability in the recognition of distinctive immunofluorescence patterns in different brands of HEp-2 cell slides - Alessandra Dellavance; Wilson de Melo Cruvinel; Paulo Luiz Carvalho Francescantonio; Cristovão Luis Pitangueira Mangueira; Inês Cristina Drugowick; Silvia Helena Rodrigues; Luis Eduardo Coelho Andrade (Sociedade Brasileira de Patologia Clínica, 2013)
INTRODUCTION: Indirect immunofluorescence on HEp-2 cells is considered the gold standard for the detection of autoantibodies against cellular antigens. However, the culture conditions, cell fixation and permeabilization processes interfere directly in the preservation and spatial distribution of antigens. Therefore, one can assume that certain peculiarities in the processing of cellular substrate may affect the recognition of indirect immunofluorescence patterns associated with several autoantibodies. OBJECTIVE: To evaluate a panel of serum samples representing nuclear, nucleolar, cytoplasmic, mitotic apparatus, and chromosome plate patterns on HEp-2 cell substrates from different suppliers. MATERIALS AND METHODS: Seven blinded observers, independent from the three selected reference centers, evaluated 17 samples yielding different nuclear, nucleolar, cytoplasmic and mitotic apparatus patterns on HEp-2 cell slides from eight different brands. The slides were coded to maintain confidentiality of both brands and participating centers. RESULTS: The 17 HEp-2 cell patterns were identified on most substrates. Nonetheless, some slides showed deficit in the expression of several patterns: nuclear coarse speckled/U1-ribonucleoprotein associated with antibodies against RNP (U1RNP), centromeric protein F (CENP-F), proliferating cell nuclear antigen (PCNA), cytoplasmic fine speckled associated with anti-Jo-1 antibodies (histidyl synthetase), nuclear mitotic apparatus protein 1 (NuMA-1) and nuclear mitotic apparatus protein 2 (NuMA-2). CONCLUSION: Despite the overall good quality of the assessed HEp-2 substrates, there was considerable inconsistency in results among different commercial substrates. The variations may be due to the evaluated batches, hence generalizations cannot be made as to the respective brands. It is recommended that each new batch or new brand be tested with a panel of reference sera representing the various patterns.